Investigating the Safety Challenges of Unmanned Aerial Vehicles (UAVs) in the Construction Environment - Khalid, Mohammad (East Carolina University, 2021)
The technologies associated with Unmanned Aerial vehicles (UAVs) have revolutionized the construction industry, simultaneously demanding a comprehensive understanding of the underlying safety implications in order to reduce the risk of personal injury, property damage, lost productivity, and financial damage. Construction is one of the most hazardous sectors, with a wide range of complexity inherent in the nature of its activities, and widespread integration of UAVs without adequate safety management expertise, training, and strategies may exacerbate existing hazards. An increasing volume of research is being conducted on the potential benefits of UAV utilization. However, there is a scarcity of knowledge and development of UAV-based safety frameworks, which might have an impact on the construction sector in the near future. This study aims to investigate the potential safety risks presented by UAV use in the construction environment. In the lack of quantitative and structured data on the effects of UAV-related incidents in the construction environment, the workforce is exposed to an array of unwarranted safety risks. The data was collected through a questionnaire survey that was constructed by a series of designed questions to provide quantitative results in a context aligned to the original research goal. The findings identify a variety of potential and actual risks associated with UAV integration, as well as a substantial perception difference concerning UAVs across industry practitioners. Collision with person and property, trespassing, system malfunction, and inexperienced pilot are the safety risks of high importance with high potential to cause substantial damage and halt productivity. The study further created a construction-specific UAV safety training program that addressed the identified risks and hazards, with the goal of increasing familiarity with UAV uses in conjunction with construction dynamics. Adopting the research study's results and improvements would allow construction practitioners to rapidly detect UAV-based safety concerns with the help of special training and excel in construction safety performance without compromising productivity.
Keywords: UAV; Safety; Hazard; Construction industry--Health aspects; Construction industry--Technological innovations; Drone aircraft--Risk assessment; Construction workers--Training of; Construction workers--Health and hygiene